Athena: nuevas armas para una diosa antigua, o los nuevos territorios de la historieta cubana - Pérez Cano, Tania (EDITORIAL DE LA UNIVERSIDAD NACIONAL DEL SUR, 2021)
This paper analyzes the webcomic Athena, by Yussuán Remolina Amador “Just-Swamp” and Daniel Cruces-Pérez, as both a symptom and a result of the transnationalization process that Cuban culture started to undergo during the 1990s. After the fall of the Berlin Wall and the Socialist European bloc, the younger generations of Cuban cartoonists distanced themselves from the limitations and political and ideological patterns that defined the sequential art after the Revolution of 1959. The new formats and topics of Cuban comics are explored in this article through interviews with the creators and a comparative analysis between the 1990s context and the present. Some of the aspects taken into account are the economic crisis during the so-called “Special Period”, the massive migratory movement that happened then, and above all, the emergence of a transnational space in which Internet and social media play an important role.